MULTIPLE INTELLIGENCE AND STUDENTS’ LEARNING MOTIVATION THROUGH DEMONSTRATION WITH OUTDOOR ACTIVITIES - Lilis Lismaya (Indonesian Journal of Learning and Instruction, 2020)
This research is motivated by learning that is still dominantly carried out in the classroom, learning emphasizes more on the aspects of knowledge, so students feel bored and lack the awareness to care for the environment well, lack of concern for the surrounding environment. The ability of students who are still lacking in terms of classifying the types of plant leaves shows Biology learning requires a different learning method, one of which is using the Demonstration with Outdoor Activities Method. The purpose of this study is to analyze Multiple Intelligence and Student Learning Motivation through Demonstration Method with Outdoor Activities. The research method used is weak experimental research design The One-Group Pretest-Posttest Design. The instruments used in this study were multiple intelligence questions, observation sheets and questionnaires. The results showed that the application of the Demonstration with Outdoor Activities Method can increase multiple intelligence and Student Learning Motivation, because the Demonstration with Outdoor Activities Method is learning done outside the classroom by means of students practicing and being invited to look for material learned, so learning does not feel boring. Based on the results of the study, it was concluded that there was an increase in Multiple Intelligences and student learning motivation through the application of the Demonstration with Outdoor Activities method.Keywords: multiple intelligence; motivation; demonstration; outdoor activities.